Pomiar lęku po porodzie. Polska wersja Postpartum Specific Anxiety Scale – Research Short Form - Jasielska, Aleksandra; Wojciechowska, Małgorzata; Maksymiuk, Renata Anna (Człowiek i Społeczeństwo, 2025)
This paper presents a study on the Polish version of the English-language scale for measuring postpartum anxiety experienced by women. It is called the Postpartum Specific Anxiety Scale – Research Short Form (PSAS-RSF). The work included translating the questionnaire into Polish and assessing its psychometric properties, such as reliability and accuracy, and factor analysis. The study was carried out with 92 midwives residing in the postnatal ward. The women assessed how often they experienced anxiety related to childcare and motherhood during the first year of the infant’s life. The study used the 16-item PSAS-RSF questionnaire, which has four subscales. To verify the external validity of the tool, the relationship of postnatal anxiety with transdiagnostic psychological constructs such as ruminations and early childhood maladaptive schemas was examined. The results suggest significant associations between postpartum anxiety and ruminations and early childhood maladaptive schemas. It was noted that women who gave birth for the second time reported lower levels of postpartum anxiety than those who gave birth for the first time. It was observed that women who gave birth for the second time declared lower levels of postpartum anxiety than those who gave birth for the first time. The conclusion is that the Polish abbreviated Postnatal Anxiety Scale (SLP-16) version has satisfactory psychometric properties. It consists of two subscales, caregiving anxiety and maternal maladaptation, and can be successfully used to measure postpartum anxiety in research and screening studies. Korekta autora: W dniu 3.11.2025 r. w Tabeli 2. zatytułowanej "Ładunki czynnikowe SLP-16” została wprowadzona korekta polegająca za zamianie poszczególnych pozycji skali na opis ich treści.